Declustering of key-based partitioned signature files. - Ciaccia, Paolo; Tiberio, Paolo; Zezula, Pavel
Access methods based on signature files can largely benefit from possibilities offered by parallel environments. To this end, an effective declustering strategy that would distribute signatures over a set of parallel independent disks has to be combined with a synergic clustering which is employed to avoid searching the whole signature file while executing a query. This article proposes two parallel signature file organizations, Hamming Filter (HF) and Hamming + Filter (H+F), whose common declustering strategy is based on error correcting codes, and where clustering is achieved by organizing signatures into fixed-size buckets, each containing signatures sharing the same key value. HF allocates signatures on disks in a static way and works well if a correct relationship holds between the parameters of the code and the size of the file. H+F is a generalization of HF suitable to manage highly dynamic files. It uses a dynamic declustering, obtained through a sequence of codes, and organizes a smooth migration of signatures between disks so that high performance levels are retained regardless of current file size. Theoretical analysis characterizes the best-case, expected, and worst-case behaviors of these organizations. Analytical results are verified by experiments on prototype systems.
Keywords: Error correcting codes; Information retrieval; Parallel independent disks; Partial match queries; Performance evaluation; Superimposed coding